COST-BENEFIT ANALYSIS OF THE PT. PAL’S SUBMARINE PROJECT DEVELOPMENT IN REALIZING DEFENSE INDUSTRY INDEPENDENCE - Arif Sutansyah Tambunan; Rudi Lazuardi; Elisabeth Tanti Pudiastuti (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Based on Law no. 16 of 2012 and the Decree of the Indonesian Defense Industry Policy Committee, PT. PAL is the lead integrator of the Main Tool of the Navy Weapon System. After the manufacture of 2 (two) submarine units, which are Ardedali-404 and Alugoro-405, at the PT. PAL in collaboration with the South Korean Daewoo Shipbuilding & Marine Engineering Co., Ltd (DSME) the company planned to build the 4th to 12th new submarine units that will be implemented starting in 2021 until 2042. The purpose of this study was to identify and determine the result of the Benefit-Cost Analysis in considering the submarine project's positive effect on PT. PAL is the independent defense industry. The method used is a qualitative method supported by Analytical Hierarchical Process (AHP) tools and Benefit-Cost Ratio (BCR)theory to analyze the result. Based on the results showed that the weight of the highest benefit criteria is B-2 (Independence of PT. PAL as a defense industry) which indicates that the point of realizing independence in Indonesia's Defense Industry can be considered as the main important aspect as it may be followed by other progress or development to support national defense in Indonesia. Then, the weight of the highest cost criteria is C-1 (Transfer of Technology (ToT) is not fully implemented) which means the cost that is need to be considered in realizing the independence of PT. PAL as the defense industry is not fully implemented in Indonesia. Finally, the chosen alternative is A-1, which is to continue cooperation in the construction of the Submarine Project would be better if it is supported by the commitment of the company and government, especially in facing the cost of reaching the benefit as described before. So, the policy that needs to be taken is to continue the next submarine-building project.